2017
DOI: 10.1111/appy.12282
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and strong association of high somatic symptom severity with depression and anxiety in a Chinese inpatient population

Abstract: The symptom profile and high prevalence of HSSS, and its association with clinically significant depression and anxiety in this inpatient population were mostly consistent to that documented by studies in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…It is directly related to the sense of well-being, quality of life, and health care expenses [ 10 , 11 ]. The study of somatic symptom burden has attracted the interests of researchers from different parts of the world and researchers have studied it in common clinical conditions such as anxiety, depression, chronic obstructive pulmonary disease (COPD), and cardiac illnesses [ 12 - 14 ]. In a large study involving 1,329 patients with anxiety and depression disorders, it has been found that 72.2%, 20.7%, and 7.1% of patients had a minimal/mild, medium, and high level of somatic symptom severity, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is directly related to the sense of well-being, quality of life, and health care expenses [ 10 , 11 ]. The study of somatic symptom burden has attracted the interests of researchers from different parts of the world and researchers have studied it in common clinical conditions such as anxiety, depression, chronic obstructive pulmonary disease (COPD), and cardiac illnesses [ 12 - 14 ]. In a large study involving 1,329 patients with anxiety and depression disorders, it has been found that 72.2%, 20.7%, and 7.1% of patients had a minimal/mild, medium, and high level of somatic symptom severity, respectively [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of somatic symptom burden has attracted the interests of researchers from different parts of the world and researchers have studied it in common clinical conditions such as anxiety, depression, chronic obstructive pulmonary disease (COPD), and cardiac illnesses [ 12 - 14 ]. In a large study involving 1,329 patients with anxiety and depression disorders, it has been found that 72.2%, 20.7%, and 7.1% of patients had a minimal/mild, medium, and high level of somatic symptom severity, respectively [ 12 ]. In another study involving COPD patients, it was found that minimal/mild, medium, and high level of somatic symptom severity was present in 45.5%, 27.3%, and 27.3% of the patients studied, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Items can be summed up to generate a continuous measure of depressive symptoms. A cut-point of 10 is used to indicate at least moderate level of depressive symptoms [22]. The Chinese version of PHQ-9 had a sensitivity of 93.33% and a specificity of 96.83% for major depression [23].…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the three Chinese versions of GAD-7, PHQ-9 and PHQ-15 recommended by DSM-5 were used as research tools in this study. Several previous studies [16,20,21] confirmed that the three scales could be used to screen anxiety, depression and somatization symptoms and assess the severity of anxiety, depression and somatization with good validity and reliability respectively in general hospitals in China.…”
Section: Discussionmentioning
confidence: 87%